Development of a Web-Based Library Information System Using the Waterfall Method to Improve the Efficiency of Book Lending Services - Andika Chozin Asyrori; Dina Cahya Pratiwi (COREAI: Jurnal Kecerdasan Buatan, Komputasi dan Teknologi Informasi, 2026)
Libraries play a vital role as information centers, but manual management often leads to challenges such as recording errors, delays in the borrowing process, and low service efficiency. This study aims to develop a web-based library information system in an educational library environment to improve the speed and accuracy of services. The waterfall method was used as the development approach, comprising the stages of requirements analysis, design, implementation, and testing. Implementation was carried out using PHP with the CodeIgniter framework and a MySQL database. The results of the study show that the system is capable of providing key features such as book search, online borrowing and returns, book and member data management, and transaction verification by the administrator. Black-box testing showed that all system functions operate in accordance with user needs. Thus, the developed system has been proven to improve operational efficiency, speed up transaction processes, and minimize recording errors in library services.